Analisis Pengaruh Investasi dan Tenaga Kerja Terhadap Produk Domestik Regional Bruto di Kota Binjai - Andini Eka Putri (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
By using Times Series data from 2017 to 2022, this research aims to analyze and understand the impact of investment and labor variables on the GDP of Binjai City. A quantitative approach was used in this research by utilizing data from two sources, namely the Central Statistics Agency (BPS) and NSWI. The method applied is ordinary least squares with the classic assumption test, as well as data processing using E-Views 12 software. The research results show that investment has a probability value of 0.92, which is much greater than 0.05. This is supported by the t-calculation value, which is smaller than the t-table (-0.108876 < 3.18245), which indicates that investment has a negative and significant impact on the GRDP of Binjai City. Meanwhile, the labor value is 0.55 > 0.05, indicating that labor has a negative and significant impact on the GDP of Binjai City, as reflected in the comparative value of t-count and t-table (0.666775 < 3.18245). Furthermore, when the two variables are evaluated simultaneously, the F probability value of 0.670525 is greater than 0.05. This indicates that, together, these two variables do not have a significant impact on GRDP in Binjai City.